On the Existence of Global Weak Solutions for a Weakly Dissipative Hyperelastic Rod Wave Equation - Haibo Yan; Ls Yong; Yu Yang; Yang Wang (Journal of Applied Mathematics)
Assuming that the initial value v0(x) belongs to the space H1(R), we prove the existence of global weak solutions for a weakly dissipative hyperelastic rod wave equation in the space C([0,∞)×R)⋂‍L∞([0,∞);H1(R)). The limit of the viscous approximation for the equation is used to establish the existence.